Study on teacher performance determinants - Muhammad Ridwan; Sitti Rizki Mulyani; Rio Andhika Putra; Neni Sri Wayuni Ningsih; Vicky Brama Kumbara (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The objective of this research was to see how salary, leadership support, and work-life balance affected teacher effectiveness. The non-probability sampling approach was applied, as well as a purposive sampling strategy. A total of 150 instructors from Padang City, West Sumatra, were employed in this study. SEM and AMOS 24.0 software were utilized in this study's analysis. Compensation has a considerable impact on teacher performance, according to the findings. Teachers' salary has a huge impact on their work-life balance. Support from leaders has a huge impact on teachers' work-life balance. Support from leaders has a substantial impact on teacher performance. Teachers' performance is unaffected by work-life balance. Compensation and leader support have a significant effect on teacher performance, compensation and leader support have a significant effect on work-life balance, and work-life balance has no significant effect on teacher performance, according to the results of this study. Various disputes and challenges will occur as a result of striking a balance between the "work" and "non-work" domains, which must be addressed by persons with families. Work-life balance cannot increase an employee's effectiveness at work. Employees that are able to manage their work and personal life may not necessarily perform better.